A influência da temperatura de pré-aquecimento e tecimento na microestrutura e propriedades mecânicas na soldagem MIG/MAG robotizada de aços SAE 8620 com ABNT LN28 - Perez, Fabiano Ricardo da Costa [UNESP] (2007)
The objective of this work is to analyze the reality scientifically found in the groud of factory of a manufacturing company of heavy agricultural equipments compared to the cares theoretically requested in the robotic GMAW of two dissimilar steels, the ABNT LN28 steel and a low alloy steel, the SAE 8620 steel. It is recommended of the literature that in the welding of the steel SAE 8620 the preheating in used, in that way it will be analyzed the influence of the preheating temperature and of the torch weaving movement in the microstructure and in the resistance of the welded joint. For that objective they will be soldiers several test specimens under different preheating temperatures and weaving conditions. In the analysis of the resulting microstructure will be considered the heating affected zone composed by the material SAE 8620 and the melted area and the resistance the traction of the welded joint obtained in the process. We will conclude that it is not advisable, in the factory groud, to use of preheating and to do deepened studies as the influence of the torc weaving movement, being considered that those variables didn't affect the microstructure and resistence of the welded joint prejudicially and any disposition in opposite would endear the proces unnecessarity.